O corpo e a política na poética fílmica de Fernando Belens - Souza, Marise Berta de (2017)
The article investigates the creative process and the filmic poetics of Fernando Belens. It is intended to observe his aesthetic choices implied in two recurring assertions in his filmography: the body and the politics. For this will be highlighted elements present in his short films reiterated in his first feature film, Pau-Brazil (2009/2014). It is concluded that in the work of Fernando Belens representations of the ways of the body and of politics are legitimating their path